Exploiting Anion–π Interactions for Efficient and Selective Catalysis with Chiral Molecular Cages. (22nd June 2021) - Luo, Na; Ao, Yu‐Fei; Wang, De‐Xian; Wang, Qi‐Qiang
Abstract: Exploiting anion–π interactions in catalyst design is a fascinating direction to develop new and fundamental catalysis. For the appealing yet flexible π‐face activation, can two or more π‐acidic surfaces be manipulated for cooperative activation to achieve efficient transformation and particularly selectivity control is highly desirable. Here, we demonstrate a supramolecular π‐catalysis strategy by establishing cooperative π‐face activation in a confined electron‐deficient cage cavity. The catalysts have a triazine based prism‐like cage core and pendant chiral base sites. Only 2 mol % of cage catalyst efficiently catalyzed the decarboxylate Mannich reactions of sulfamate‐headed cyclic aldimines and a series of malonic acid half thioesters in nearly quantitative yields and up to 97 % ee, enabling an unprecedent organocatalytic approach. The supramolecular π‐cavity is essential in harnessing cooperative anion–π interactions for the efficient activation and excellent selectivity control. Abstract : A strategy by building cooperative anion–π interactions in a confined cage cavity to drive efficient and selective catalysis was established. Only 2 mol % of easily made chiral cages enabled excellent conversions and up to 97 % ee in catalyzing a class of decarboxylate Mannich reactions, which was unrealized with conventional organocatalysts.